2012
DOI: 10.1111/j.1540-6520.2012.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Perceptions and Intentions: The Role of Gender and Culture

Abstract: This paper examines how culture and gender shape entrepreneurial perceptions and intentions within Hofstede's cultural dimensions framework and gender role theory. We test whether gender differences exist in the way university students in three nations perceive barriers to entrepreneurship and whether gender has a moderating effect on the relationship between perceived barriers and entrepreneurial intentions across nations. Findings indicate significant gender differences in barrier perceptions. However, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
587
5
40

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 657 publications
(662 citation statements)
references
References 80 publications
30
587
5
40
Order By: Relevance
“…There is also evidence that perceived barriers may hinder entrepreneurs in becoming more involved in the entrepreneurial process (Van der Zwan et al 2013;Grilo and Thurik 2008;Orser et al 2000). While previous research has focused on the relationship between perceived barriers and entrepreneurial intentions (Shinnar et al 2012;Kuckertz and Wagner 2010), follow-up research could focus on how perceptions at start-up affect the experiences of sustainable entrepreneurs during the process of growing their business, including different performance measures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is also evidence that perceived barriers may hinder entrepreneurs in becoming more involved in the entrepreneurial process (Van der Zwan et al 2013;Grilo and Thurik 2008;Orser et al 2000). While previous research has focused on the relationship between perceived barriers and entrepreneurial intentions (Shinnar et al 2012;Kuckertz and Wagner 2010), follow-up research could focus on how perceptions at start-up affect the experiences of sustainable entrepreneurs during the process of growing their business, including different performance measures.…”
Section: Discussionmentioning
confidence: 99%
“…We also control for age, education, and household income. A negative relationship exists between the perceived lack of entrepreneurial support and entrepreneurial intentions (Shinnar et al 2012), and intentions have been shown to depend on age, education, and income in previous literature (Lee et al 2011). In addition, entrepreneurial perceptions seem to be different across cultures (Shinnar et al 2012), which justifies the inclusion of country dummies.…”
Section: Control Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Carter, Brush, Greene, Gatewood, & Hart, 2003;Goby & Erogul, 2011;Minniti, 2008);political and economic stability (Lerner, 2010;Movahedi & Yaghoubi-Farani, 2012;Taylor & Plummer, 2003);culture and society's views on entrepreneurship (C. C. Baughn et al, 2006;C. Baughn & Neupert, 2003;Gupta, Turban, Wasti, & Sikdar, 2009;Light & Dana, 2013;Ramadani, Gërguri, Dana, & Tašaminova, 2013;Shinnar, Giacomin, & Janssen, 2012);business information (Ettl & Welter, 2010;Sandhu et al, 2011);support mechanisms and networking opportunities (Ahmad & Xavier, 2011;Al-Alak & Al-Haddad, 2010;Caputo, Mehtap, et al, 2015;De Vita et al, 2014;Goby & Erogul, 2011);access to formal education and training (Dabic et al, 2012;Dickson, Solomon, & Weaver, 2008;Lüthje & Franke, 2002;Packham, Jones, Miller, Pickernell, & Thomas, 2010;Pruett, 2012).…”
Section: Entrepreneurial Intention and Female Entrepreneurshipmentioning
confidence: 99%